ABORSI: ANTARA DIALEKTIKA MORAL DAN KEBIJAKAN HUKUM PIDANA INDONESIA - ASHADY, SUHEFLIHUSNAINI; DUDY, ARYADI ALMAU (GANEC SWARA, 2023)
This research examines the moral and legal dialectics in viewing abortion as well as the construction of abortion policy in the Indonesian criminal law system after the passing of Law Number 1 of 2023 concerning the Criminal Code and Law Number 17 of 2023 concerning Health. The method used is a normative research method with a statutory and conceptual approach. The research results show that abortion cannot only be viewed in legal terms, but it is important to pay attention to moral aspects. Law is a law that is filled with morality so that it does not result in conflict between norms and society. Morality is the main source of law, especially in Indonesia which is based on Pancasila in all aspects of state life. Next, Indonesia's criminal law policy allows abortion under strict conditions, namely if the woman is a victim of a crime of rape or other crime of sexual violence that causes pregnancy, the gestational age does not exceed the permitted age, and/or has indications of a medical emergency. If the conditions are not met, then the perpetrator of the abortion, whether the main perpetrator, the participating perpetrator, and the person who assists in carrying out the abortion, can be punished